Pendampingan Kader Posyandu dalam rangka Deteksi Dini BBLR dengan Metode URLABANDUS (ukur LILA, Timbang BB dan Ukur Tinggi Fundus Uteri) pada ibu hamil TM 3 - Eko Sri Wulaningtyas; Entin Srihadi Yanti; Ardina Rezky Noeraini; Mulazimah Mulazimah; Dhewi Nurahmawati; Norma Risnasari; Adelia Widyaning Tyas; Asmaul Fauziah (Pusat Riset dan Inovasi Nasional, 2023)
Babies who have low birth weight (LBW) are a very complex and complicated problem because they contribute to poor health because they not only cause high mortality rates, but can also cause disability, impairment, or inhibit cognitive growth and development, and chronic diseases. in the future, this is due to the unstable condition of the baby's body. Several studies have shown that LBW greatly determines health in the future. Babies born weighing less than 2500 grams are closely related to degenerative diseases in adulthood. LBW are more prone to obesity and are at risk of suffering from NCD (Non Communicable Diseases) in adulthood, therefore to improve the quality of one's health should be started as early as possible since the fetus is in the womb. The purpose of this community service activity is to increase the knowledge of Posyandu Health Cadres about early detection of LBW events since in the womb. This Community Service activity involves Posyandu Health Cadres, namely in the village of Ringinsari, implementation has been carried out in January-March 2023. The service is carried out starting from preparation to completion. Evaluation. The method used in the service is the method of socialization and application (applicative) directly in the field. The results of the evaluation show that there is an increase in the ability of Posyandu health cadres to carry out early detection of LBW events since in the womb with the URLABANDUS method